Optimization of Gas Adsorption Porosimetry for Geopolymer Analysis. Issue 11 (20th September 2013) - Glad, Brayden E.; Kriven, Waltraud M.
Abstract : Gas adsorption porosity measurement of geopolymers (GPs) is required for quantitative understanding of such mesoporous structures, but the complex nature of the GP system makes analysis difficult. Previous results in the literature are often ambiguous or contradictory. A systematic investigation of metakaolin GP gas adsorption results was conducted to optimize the use of this measurement technique and verify that results match known theory about GP structure. It was found that GP undergoes structural change upon degassing at 100°C or higher. If and only if this change is prevented by degassing at a lower temperature could it be shown that specific surface area and total gas adsorption increases with both increasing curing temperature and decreased Si:Al ratio. This observation is consistent with previous suggestions of increased zeolitic character under these conditions, where previous gas adsorption investigations had not observed this expected relationship. Hydrogen physisorption is proposed as a substitute technique for micropore isotherms in GPs due to the difficulty of removing trace gasses from GPs and the measurement effect of such gasses at high vacuum. A hydrogen physisorption isotherm qualitatively resembled an equivalent nitrogen micropore isotherm.